Effect of T-Touch on behavior of saddle horses - Padalino, B.; Siniscalchi, M.; Lusito, R.; Quaranta, A. (Embracing science to enhance equine welfare and horse-human interactions, 2013)
Tellington method (T-Touch®) is usually practiced in the equine field with the goal to improve equine welfare and the relationship between rider and his horse. To our knowledge this is the first scientific work on this topic. The effects of T-Touch® on the behavior of 20 saddle horses (aged 6-18 years) were investigated; no subjects had previous experience with this technique. Horses were studied in 3 situations lasting 20 minutes each: T-Touch, massage/petting (M/P), resting (R). All phases were recorded by a video-camera. The frequency of the following behaviors was scored: autogrooming, deep breathing, relaxing of the neck, kicking, pawing, licking/chewing, head tossing, biting and lateral/forward/ backward movements. The videos were analyzed by 10 persons, 5 Scientifics and 5 not, using a Behavioral Score (BS) from 1 (highly negative response) to 5 (highly positive response). GLM analyses for repeated measures revealed a significant main effect of the following behaviors: autogrooming F(2,38)=9.016, P<0.01; deep breathing F(2,38)=4.01, P=0.02; neck relaxing F(2,38)=12.904, P<0.01; F(2,38)=9.016, P<0.01; kicking F(2,38)=3.301, P=0.04; pawing F(2,38)=4.594, P=0.01 and licking F(2,38)=3.715, P=0.03. Post-hoc analyses (Fisher`s Protected LSD) revealed that autogrooming and neck relaxing behaviors were higher during T-Touch than R (P<0.01) and M/P (P<0.05); in addition, pawing occurrence was higher during R respect to M/P (P<0.05) while kicking frequency was higher during M/P respect to R (P<0.05). Finally, the highest frequency of licking was achieved during R (P<0.05) and the lowest frequency of deep breathing was measured during M/P (M/P vs TTouch P<0.01; M/P vs R P<0.05). Regarding the BS, results clearly showed that horses appeared more relaxed during the T-Touch procedure respect to massage/petting (t(18)=7.742, P<0.00). In general our results showed that T-Touch® was positively accepted by saddle horses without eliciting any aggressive behavioral responses. Further studies need to more deeply understand the effects of T-Touch on endocrinal and physiological parameters. Layperson`s paragraph: During T-Touch horses didn`t show any aggressive behaviors & showed more relaxing of the neck, deep breathing & autogrooming compared with the petting and resting situations; this technique could improve equine welfare and rider-horse relationship.